A comprehensive review on the new developments consideration in a stir casting processing of aluminum matrix composites. (2022) - Singh, Hartaj; Singh, Kapil; Vardhan, Sachit; Mohan, Sanjay
Highlights: The objective of this research article is to explore the new developments consideration in a stir casting processing of aluminium matrix composites. The critical review emphasizes in the existing and some newest developments are carried-out by several researchers in a stir casting processing. In this study, the current scenarios of aluminium matrix composite and continuous newest developments and existing challenges in stir casting processing have also been explored. Abstract: Ceramic based aluminum matrix composites have numerous industrial applications existing in the aerospace, marine, automobile, power plant, domestic and electronics utensils attributable to a tremendous specific strength and wear resistance properties. Aluminum matrix composites materials reveal several physical and mechanical properties. Many manufacturing processes are offered for the fabrication of aluminum matrix composites, melt stirring is recognized as a predominantly capable process, and its advantages turn over in its effortlessness and flexibility to a massive manufacturing. The critical review emphasizes in the existing and some newest developments are carried-out by several researchers in a stir casting processing. In this study, the current scenarios of aluminum matrix composite and continuous newest developments and existing challenges in stir casting processing have also been explored moreover, some more work needed for improvements of stir casting processing of composites is to be proposed in the future.